BО‘LAJAK MUTAXASSISLARNI INNOVATSION FAOLIYATGA TAYYORLASHNING TASHKILIY-TUZILMAVIY MODELI - Axmedov, J.R. (SCIENCE and SOCIETY, 2024)
In this article, based on an analysis of the content of innovative activities and the scientific and practical aspects of preparing them for this activity, an organizational and structural model of preparing future teachers for professional activities has been created.